Social Situation Analysis During The Pandemic Outbreak In The Novel The Stand By Stephen King - Ali, Muhammad Ilham; Herminus Efrando Pabur; Ceisy Nita Wuntu (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This research aims to analyze the social situation during the flu-influenza pandemic in the novel